Peran Public Relations dalam Mengatasi Manajemen Krisis: Studi Kasus Public Relations Officer Lion Air Group - Ignes Ambarwati; Mochammad Mirza; Ari Suseno; Alamsyah Alamsyah (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
PT. Lion Mentari Airlines (Lion Air) was founded on November 15 1999 and began operations on June 30 2000. By serving flight routes from Jakarta to Pontianak using Boeing 737-200 type aircraft. Lion Air has a philosophy that consumers are truly sovereign (consumer sovereignty) with the slogan